POLA KOMUNIKASI GURU DAN ORANG TUA UNTUK MENINGKATKAN KUALITAS BELAJAR PESERTA DIDIK - Dalilah, Dwi Dipta; Utami, Nadila; Syauqiyyah, Yasyifa Azhar (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to describe the pattern of teacher communication and parents to improve the quality of students’ learning at State Elementary School 1 in Pandanglang-Banten. This research uses qualitative method/case studies. In this study involves IIIA homeroom teacher, parents and students, as research participants. The data was obtained through interviews and observations. From the results show that the pattern of teacher and parent communication to improve the quality of learning of students, in IIIA class occurs between the parents and teachers in this school, with the existence of an organisai/association made by parents. One of the goals is to determine the learning activities and information about students at school. If there is no communication between the teacher and the parents at school, there will cause misconcept between teachers and parents, so that it can affect students. Therefore, the communication pattern at school is very necessary, to support what things happen to students, because success and learning quality of students is the result of cooperation between teachers and parents. Therefore, it takes a pattern of communication and parents.